Dual-tree complex wavelet transform applied to fault monitoring and identification in aeronautical structures - Abreu, C. C.E. [UNESP]; Chavarette, F. R. [UNESP]; Villarreal, F. [UNESP]; Duarte, M. A.Q.; Lima, F. P.A. [UNESP] (Academic Publications, 2014)
This paper proposes the application of the dual-tree complex wavelet transform on fault monitoring and identification in aeronautical structures. For this purpose, a multiscale analysis from phase of the complex wavelet coefficients is proposed. Phase is very sensitive to variations of the signal capturing small flaws. Furthermore, magnitude provides information about the intensity of failure. Simulation results from a beam model showed that the proposed method achieved good performance in small flaws identification.
Keywords: Aeronautical structures; Dual-tree complex wavelet transform; Fault monitoring and identification